Role distance. An ethnographic study on how street-level managers cope - Wong, J (Oxford University Press, 2023)
Policy is not only made by street-level bureaucrats at the frontlines. It is also made by their superiors—street-level managers—who set the organizational conditions through which street-level bureaucrats act. Although scholars have documented how street-level bureaucrats cope with the pressures of their work by, for instance, breaking or bending rules, the question of how street-level managers cope with the pressures of their own work has received less attention. Drawing from ethnographic data of a network of publicly funded health centers in the Midwestern US, I show how street-level managers use an interaction ritual with role distance to cope. Role distance is mobilized when the person uses communicative expressions such as laughter or cries of frustration to convey a critical distance from what her organizational role prescribes. Based on classic sociological insights, I posit that role distance can function as follows. It can help managers preserve self by allowing them to define their putatively “more-human self” from their work, create a feeling of collectiveness as they orient themselves to the shared frustrations yet obligations that their role engenders, which enables them to coordinate on carrying out tasks, even those that rub against their preferences and well-intentions. Taken together, I suggest that role distance can offer a coping function, which enables them to hold in abeyance individual and collective responsibility for the decisions they make. I then highlight the benefits and unintended consequences of role distance and posit what academics and practitioners can do to ensure that street-level managers use role distance toward more productive ends.